Pengukuran Tingkat Risiko dan Keamanan Informasi Menggunakan Metode FMEA Berbasis ISO/IEC 27001 pada Instansi XYZ untuk Keamanan Sistem Informasi - Kusnandar, Aris; Rochim, Adian Fatchur; Gunawan, Vincensius (Jurnal Sistem Informasi Bisnis, 2024)
The more information stored in an organization, the higher the risks that may arise, such as damage, loss, or the exposure of personal information to irresponsible parties. XYZ Institution faces information security threats from various sources, including data theft, damage, and computer hacking. It is essential for the organization to understand the level of information security risk to ensure information remains secure. Therefore, this study proposes measuring information security risk using the FMEA method and analyzing information security risks based on ISO/IEC 27001:2013. The aim of this study is to identify and assess the level of information security risk at XYZ Institution to provide recommendations for information security. The study's results revealed 4 high-risk information security threats, 9 medium-risk threats, and 16 low-risk threats. The findings demonstrate that the organization needs to pay more attention to information security to ensure its smooth operation in the future.